Free-living cutaneous amebiasis, ignored herald of lethal encephalitis. Case report - Celis, Violeta (2023)
Introduction: Diseases caused by free-living amoebas (FLA) are rare but with a lethality greater than 90% when they affect the central nervous system (CNS). The clinical picture can be confused with more prevalent diseases. Case report: A 32-year-old farmer from Poroto-Trujillo-La Libertad-Peru, started the disease with a central facial erythematous plaque that was diagnosed as cutaneous tuberculosis (CTB), without improvement despite receiving a complete regimen of anti-tuberculous chemotherapy. Seven months later, he presented severe encephalitis and died three days after his admission to the hospital. FLA trophozoites were found in the skin biopsy. A diagnosis of cutaneous dermatitis due to FLA complicated with granulomatous amebic encephalitis (GAE) is proposed. Similar cases have not been documented in his place of origin. Conclusion: In northern Peru, skin plaques in people exposed to the ground or stagnant water should be considered warning signs of the probability of AVL infection.